Anxienty and neurotizm degree correlation with values of the life satisfaction level in vibration disease - Ye. A. Ganovich; V. A. Semenikhin; M. G. Zhestikova (Бюллетень сибирской медицины)
Aim of the study was the determination of the personal and situational anxiety, neurotizm and life satisfaction levels. Study’s materials were 146 patients with vibration disease. All patients underwent the neuropsychologic analysis. Increased anxiety level as the stable personality characteristic was registered in all subgroups of the main group. Described above changes speak for the practicability of the active detection of the affective qualm sphere’s disorders in this cohort of patients with subsequent medicated and non-medicated correction.